1980
DOI: 10.1002/ajh.2830080106
|View full text |Cite
|
Sign up to set email alerts
|

Murine recovery from busulfan‐induced hematopoietic toxicity as assessed by three assays for colony‐forming cells

Abstract: These studies were designed to explore further the interrelationships between various stem cell and other hematopoietic compartments of the mouse. Busulfan (BU) has been shown by others to have a profound effect on the transplantable pluripotent stem cells capable of forming colonies on spleens (CFU) of lethally irradiated recipients -more so than on cells of differentiated compartments. Another presumed assay of pluripotent stem cells consists of counting colonies on spleens of nontransplanted sublethally irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This residual marrow damage would not be predicted by parameters such as bone marrow cellularity, peripheral blood counts or even in some cases by CFU-S numbers (20,36). However "stressors" such as serial transfer of marrow (20), anemia (21) or irradiation (19) have.revealed that these mice have a more limited hemopoietic response than controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This residual marrow damage would not be predicted by parameters such as bone marrow cellularity, peripheral blood counts or even in some cases by CFU-S numbers (20,36). However "stressors" such as serial transfer of marrow (20), anemia (21) or irradiation (19) have.revealed that these mice have a more limited hemopoietic response than controls.…”
Section: Discussionmentioning
confidence: 99%
“…Marrow CFU-E numbers follow a predictive pattern, increased following bleeding (34) and decreased during plethora induced by red cell transfusions (35). Erythroid progenitors as measured by clonal assays are sensitive to cytostatic agents (30,36,37) and known marrow toxicicants such as benzene (38,39). Use of these assays has revealed that some patients with aplastic anemia possess a population of lymphocytes capable of suppressing in vitro erythroidcolony formation by normal human bone marrow (40), whereas in congenital hypoplastic (DiamondBlackfan) anemia, lymphocytes are normal, and the defect appears to reside in the erythroid progenitors (41).…”
Section: Erythroid Progenitors (Cfu-e Bfu-e)mentioning
confidence: 99%
See 1 more Smart Citation
“…A single dose of busulfan (Myleran) causes a severe and prolonged depression of all hematopoietic cell lines (1,2). Cells forming spleen colonies, either by transplantation (CFU-S) o r studied endogenously (E-CFU), are reduced to very low levels almost immediately following busulfan.…”
mentioning
confidence: 99%
“…Mice were given busulfan, followed by endotoxin, and total nucleated cells per humerus, peroxidase positive cells per humerus, and CFU-C were monitored during the succeeding 2 weeks. For a detailed consideration of the effect of busulfan alone on these measures of hematopoiesis and also on transplanted and endogenous spleen colonies, hematocrit, spleen weight, and iron uptake per spleen and humerus, please see Boggs et al (1).…”
mentioning
confidence: 99%